Pengaruh Luas Lahan, Modal, Dan Tenaga KerjaTerhadap Pendapatan Petani Nanas Di Kecamatan Panai Tengah Kabupaten Labuhanbatu - Rinaldi Rinaldi; Edison Sagala (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2024)
This research aims to determine the influence of land area, capital and labor on the income of pineapple farmers in Central Panai District, Labuhan Batu Regency. Sample used was 95 respondents. The data collection techniques used were observation, interviews and questionnaires. The data analysis technique used is a multiple linear regression model and hypothesis testing using the t test, F test and coefficient of determination. Previously the data had been tested using validity tests, reliability tests and classical assumption tests. Data processing uses the SPSS 16.0 for Windows program. The results show that land area has a significant effect on the income of pineapple farmers in Panai Tengah District, Labuhanbatu Regency, Capital has a significant effect on the income of pineapple farmers in Panai Tengah District, Labuhanbatu Regency, Labor has a significant effect on the income of pineapple farmers in Panai Tengah District, Labuhanbatu Regency, Luas Land, Capital and Labor have a significant influence on the income of pineapple farmers in Panai Tengah District, Labuhanbatu Regency.